ANALISIS PENGARUH KEBIJAKAN HUTANG TERHADAP KINERJA KEUANGAN - Wijaya, Ari Triadi; Fikri, Muhammad Ali (Jurnal Fokus Manajemen Bisnis, 2019)
This study aims to determine the effect of debt policy onÂ  financial performance of coal companies listed on the Indonesia Stock Exchange. Policy debt is proxied by short term debt (STD), long term debt (LTD), and total debt (TD), while financial performance is proxied by return on equity (ROE). This research carried out for 3 (three) years, namely 2015-2017. This research is a causal research with a quantitative approach, whereas based on the level of exploration of this study, including associative research. Population research is a coal company listed on the Indonesia Stock Exchange for the period 2015-2017. Samples obtained were based on purposive sampling technique, and obtained 21 company. Data analysis technique used panel data regression. Regression with using the free variable short term debt (STD), long term debt (LTD), and total debt (TD). Based on the results of data analysis, STD has no significant effect on ROE. Variable LTD has a significant effect on ROE. The TD variable has no significant effect with ROE. so the STD and LTD variables are able to influence the ROE variable explained by other factors outside this research model.